A review on lignin structure, pretreatments, fermentation reactions and biorefinery potential. (January 2019) - Ponnusamy, Vinoth Kumar; Nguyen, Dinh Duc; Dharmaraja, Jeyaprakash; Shobana, Sutha; Banu, J. Rajesh; Saratale, Rijuta Ganesh; Chang, Soon Woong; Kumar, Gopalakrishnan
Graphical abstract: Highlights: Valorization of lignin towards chemicals and fuels is reviewed. Various process routes are evaluated for efficient lignin depolymerization. Detrimental reactions in depolymerization of lignin are discussed. Biorefinery aspects for value added products generation are outlined. Perspectives towards the biorefinery scheme is recommended. Abstract: In recent years, lignin valorization is commercially an important and advanced sustainable process for lignocellulosic biomass-based industries, primarily through the depolymerization path. The conversion of the lignin moieties into biofuels and other high value-added products are still challenging to the researchers due to the heterogeneity and complex structure of lignin-containing biomass. Besides, the involvement of different microorganisms that carries varying metabolic and enzymatic complex systems towards degradation and conversion of the lignin moieties also discussed. These microorganisms are frequently short of the traits which are obligatory for the industrial application to achieve maximum yields and productivity. This review mainly focuses on the current progress and developments in the pretreatment routes for enhancing lignin degradation and also assesses the liquid and gaseous biofuel production by fermentation, gasification and hybrid technologies along with the biorefinery schemes which involves the synthesis of high value-added chemicals, biochar and other valuable products.